Health related quality of life and physical activity in prison: a multicenter observational study in Italy. (24th October 2017) - Mannocci, Alice; Mipatrini, Daniele; D'Egidio, Valeria; Rizzo, Jenny; Meggiolaro, Sara; Firenze, Alberto; Boccia, Giovanni; Santangelo, Omar E; Villari, Paolo; La Torre, Giuseppe; Masala, Daniele
Abstract: Background: Inmates have a poorer health status than the general population. The physical activity is well know that improve the wellness of the people. This multicentric cross-sectional study aimed to assess the relationship between Quality of Life (QoL) and physical activity levels among Italian prisoners. Methods: Inmates from eight prisons compiled a questionnaire. The Metabolic Equivalent of Task (MET) was used to measure inmates' weekly physical activity levels (MATwk). Their QoL was measured using two components of Short Form with 12 items (SF12): MCS (mental score) and PCS (physical score). Results: A total of 636 questionnaires were compiled. High level of MET was significantly ( P <0.05) associated with both PCS (OR = 1.02) and MCS (OR = 1.03). The correlations between PCS, MCS vs. METwk scores were respectively significant: r = 0.17 and r = 0.10, P <0.05. The number of years of detention was associated to higher MET (OR = 1.04 P <0.05). The presence of Physical Exercise Areas (PEAs) within Jails did not improve the QoL level. Conclusions: Jails may not seem like the ideal place to fight sedentary behavior, but, in any case, health promotion can occur within its walls. The heterogeneity of Italian jails, and particularly relative PEAs therein (areas had different characteristics between jails), suggests that such spaces should be regulated or well defined. Furthermore, the implement of training schedules could be done in a standardized way. Despite this heterogeneity both the physical and mental components of inmates' quality of life were associated to a high level of physical activity.